1995
DOI: 10.1097/00007890-199501000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Experience With Liver And Kidney Allografts From Non-Heart-Beating Donors

Abstract: Given the shortage of cadaveric organs, we began a study utilizing NHBD for OLTx and KTx. There were 24 NHBD between January 1989 and September 1993. These donors were divided into 2 groups: uncontrolled NHBD (G1) (n = 14) were patients whose organs were recovered following a period of CPR; and controlled NHBD (G2) (n = 10) were patients whose organs were procured after sustaining cardiopulmonary arrest (CA) following extubation in an operating room setting. Eight kidneys and 5 livers were discarded because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
187
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 348 publications
(190 citation statements)
references
References 11 publications
3
187
0
Order By: Relevance
“…Prolonged warm ischemic time has also been associated with irreversible bile duct damage and poorer outcomes in NHBD grafts. [17][18][19] With respect to postoperative issues, there was no significant difference in the length of postoperative hospital stay, immunosuppressive regimen, number of acute or chronic cellular rejection episodes, or development of hepatic artery stenosis noted between patients with BCS and controls. However, the number of repeat hospital admissions after BCS diagnosis and the number of required biliary therapeutic procedures were significantly greater in BCS patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prolonged warm ischemic time has also been associated with irreversible bile duct damage and poorer outcomes in NHBD grafts. [17][18][19] With respect to postoperative issues, there was no significant difference in the length of postoperative hospital stay, immunosuppressive regimen, number of acute or chronic cellular rejection episodes, or development of hepatic artery stenosis noted between patients with BCS and controls. However, the number of repeat hospital admissions after BCS diagnosis and the number of required biliary therapeutic procedures were significantly greater in BCS patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The use of NHBD grafts has been previously shown to lead to a higher incidence of biliary complications. [19][20][21] A recent study from Johns Hopkins revealed the presence of biliary casts, proximal to ductal anastomotic strictures, in 35% of its NHBD liver transplants. 22 A possible reason that our current study did not show an increased incidence of BCS in NHBD grafts is the limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The most important issue regarding this modality is the gap between an insufficient pool of organ donors and the increasing number of potential recipients 1,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, there is not a standard technique available and the means of promoting the cardiac arrest may contribute to worsen organ preservation [2][3][4]6 . Thus, new experimental models of non heart beating donating will be useful to control research bias and allow further studies on organ transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…6 A change in practice occurred when laws granting the declaration of death according to neurologic criteria led to the preferential use of organs from brain-dead donors. 7 However, some institutions continued to recover DCD organs in addition to those of brain-dead donors.…”
mentioning
confidence: 99%